GRANULOMATOSIS WITH POLYANGIITIS, WHICH IS PATHOGENETICALLY ASSOCIATED WITH ANTINEUTROPHIL CYTOPLASMIC ANTIBODIES: CLINICAL FEATURES - Tatiana Valentinovna Beketova (Научно-практическая ревматология)
The author studied in detail the specific features of the clinical manifestations reflecting a granulomatous inflammatory response and necrotizing polyangiitis, by using her experience in following up 70 patients with granulomatosis and polyangiitis (Wegener's), and analyzed their early symptoms, premorbid background, and possible predictors. Granulomatous inflammation and its related clinical manifestations (primarily orbital pseudotumor and subfold granuloma of the larynx) was demonstrated to tend over time to occupy a dominant place in the clinical picture of the disease while the proportion of the symptoms apparently related to necrotizing vasculitis was generally decreased. Interpretation of mechanisms for the development of granulomatosis with polyangiitis (Wegener's) may be of value for the further elaboration of an optimal treatment strategy.